Elastin−Calmodulin Scaffold for Protein Microarray Fabrication - Jenikova, Gabriela; Lao, U Loi; Gao, Di; Mulchandani, Ashok; Chen, Wilfred (Langmuir, 2007)
In this work, we report a new method to reversibly immobilize proteins to a surface in a functionally active orientation directly from cell lysate by employing a fusion protein consisting of a thermal-responsive elastin (ELP) domain as the surface anchor and a calcium-responsive calmodulin (CalM) domain for protein capturing. Incorporation of an M13 tag into recombinant proteins enables not only easy surface immobilization but also direct purification from cell lysates. The feasibility of concept was demonstrated using the M13-tagged yellow fluorescent protein (M13-YFP). The ELP−CalM functionalized surfaces were shown to capture M13-YFP directly from cell lysate through the specific calmodulin-M13 association in a calcium-dependent manner. We also demonstrated that immobilization is reversible; the bound proteins were released from the surface in the presence of EDTA.